2015
DOI: 10.1007/s11747-015-0462-5
|View full text |Cite
|
Sign up to set email alerts
|

Seeing relationships through the lens of psychological contracts: the structure of consumer service relationships

Abstract: Serving as mental models, psychological contracts guide consumers' service interactions with their service providers. This study incorporates a psychological contract perspective into the relationship marketing literature, exploring service customers' beliefs about the terms and conditions of the resource exchange process and the types of relationships they form with service providers. It provides new insights that explain why and how some customers respond favorably to a company's relationship overtures and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
77
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 77 publications
3
77
0
1
Order By: Relevance
“…Serious m‐games can be used to motivate and persuade households to perform socially responsible behaviors such as energy efficiency through establishing or reinforcing mutual beliefs or informal obligations regarding energy efficiency. This finding is consistent with the concept of psychological contracts, which can be formed upon a socioemotional base, whereby social and emotional experiences can support interpersonal relationships and agreements (Guo et al., ). In the case of this study, participants found experiences of using a serious m‐game enabled the construction or enforcement of psychological contracts for household energy‐efficient behaviors, which in turn lead to higher levels of motivation and persuasion to perform behaviors.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Serious m‐games can be used to motivate and persuade households to perform socially responsible behaviors such as energy efficiency through establishing or reinforcing mutual beliefs or informal obligations regarding energy efficiency. This finding is consistent with the concept of psychological contracts, which can be formed upon a socioemotional base, whereby social and emotional experiences can support interpersonal relationships and agreements (Guo et al., ). In the case of this study, participants found experiences of using a serious m‐game enabled the construction or enforcement of psychological contracts for household energy‐efficient behaviors, which in turn lead to higher levels of motivation and persuasion to perform behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, participants discussed the household values of saving energy could be verbally or nonverbally agreed among household members. These agreements appear to closely resemble psychological contracts, whereby household members share mutual beliefs, perceptions, and informal obligations as to how household energy‐efficient behaviors should be performed (Guo, Gruen, & Tang, ). The majority of participants pointed out that after playing the serious m‐game, they became more cognitively aware (Gentile et al., ) of their obligations in attempting to save energy in their household and this would lead to higher levels of motivation and persuasion to perform energy‐efficient behaviors (Klimmt, ).…”
Section: Findings and Discussionmentioning
confidence: 98%
“…The classical psychological contract literature describes two types of consumer psychological contract: the transactional psychological contract and the relational psychological contract [17]. A recent paper suggested that there are four types of contracts: relational, standard, transitional and captive contracts [5]; however, in their definitions, the features of the standard contract are similar to those of the transactional contract. Therefore, we address the two classical contract types in this paper.…”
Section: Psychological Contract and Psychological Contract Breachesmentioning
confidence: 99%
“…Citizenship behaviour is not a requirement for a successful product or service delivery, but it has positive effects on brand image and brand relationships [3]. Recent research on the interactive process of the consumer-brand relationship has typically explored it from two perspectives to acquire an in-depth understanding of this phenomenon [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, empirical research on consumer psychological contracts in the platform economy is focused on the relationship between consumers and online businesses (Pavlou and Gefen, 2005;Guo et al, 2015;Malhotra et al, 2017). Although there is some evidence on consumer perception of the responsibility of online platforms, empirical research on the consumer's psychological contract with platform enterprises is limited.…”
Section: Introductionmentioning
confidence: 99%